Glycoconjugate vaccines and immune interactions, and implications for vaccination schedules. (November 2011) - Borrow, Ray; Dagan, Ron; Zepp, Fred; Hallander, Hans; Poolman, Jan
Conjugate vaccines using diphtheria toxoid variant (CRM197 ), diphtheria toxoid and tetanus toxoid (TT) as carrier protein may induce immune interactions (interference or impairment as measured by lower antibody levels, or enhancement [higher antibody levels]) when coadministered with other vaccines. Immune enhancement occurs when two TT conjugates are coadministered. CRM197 conjugate vaccines induce immune bystander interference when given with diphtheria-tetanus-acellular pertussis vaccines, which reduces responses to coadministered Haemophilus influenzae type b vaccine conjugated to TT. These bystander effects are greater as the amount of CRM197 administered increases. When large amounts of either TT or CRM197 are coadministered, dose-related carrier-induced epitopic suppression may occur, affecting immune responses to meningococcal or pneumococcal polysaccharides. These observations have implications for vaccine scheduling. The range of available alternative vaccines means that specific vaccine coadministrations can avoid or reduce CRM197 -induced interference. Potential interactions arising from new CRM197 or TT conjugates will need to be thoroughly examined.